2004
DOI: 10.1158/1078-0432.ccr-04-0104
|View full text |Cite
|
Sign up to set email alerts
|

Ring Finger Protein 43 as a New Target for Cancer Immunotherapy

Abstract: We have performed genome-wide exploration by using cDNA microarray profiling, and successfully identified a new tumor-associated antigen (TAA) that can induce potent cytotoxic T lymphocytes (CTLs) specific to tumor cells. In our preceding study, we identified multiple new genes by using gene expression profiling with a genome-wide cDNA microarray containing 23,040 genes. Among them, we selected RNF43 (ring finger protein 43) as a promising candidate for a TAA expressed by colon cancer cells. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…The proliferation and antiapoptotic effects of RNF43 have been well established in colorectal cancer (8,21). In keeping with previous reports, we found that knockdown of RNF43 by siRNA both inhibited proliferation and induced apoptosis in HCCs.…”
Section: Discussionsupporting
confidence: 92%
“…The proliferation and antiapoptotic effects of RNF43 have been well established in colorectal cancer (8,21). In keeping with previous reports, we found that knockdown of RNF43 by siRNA both inhibited proliferation and induced apoptosis in HCCs.…”
Section: Discussionsupporting
confidence: 92%
“…We examined whether CTLs could be induced with the peptide from human PBMCs. Monocyte-derived dendritic cells were used to induce CTLs against peptides as previously described (46,47). In brief, the PBMCs were obtained from healthy volunteers with corresponding HLAs and were cultured in the presence of granulocyte macrophage colony-stimulating factor (provided by Kirin Brewery Co., Tokyo, Japan) at 1,000 units/mL and interleukin-4 (Genzyme/Techne, Minneapolis, MN) at 1,000 units/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Because we do not have access to A24/ Kb transgenic mice, we searched for class I epitopes restricted to HLA-A*2402 using only in vitro assays with human PBMCs as previously described (46). Epitope-candidate peptides were selected in the order of the binding scores, which reflected the binding affinity of the peptide to HLA class I molecules (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…RNF43 was also identified as a tumor-associated antigen of colorectal cancer (CRC). A tumor-associated antigen contains epitope peptides that promote antitumor immune response for cancer immunotherapy [14]. However, the role of RNF43 in the progression of carcinogenesis has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%